2020
DOI: 10.3389/fimmu.2020.00001
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the Innate Immune Response by Varicella Zoster Virus

Abstract: Varicella zoster virus (VZV) is the causative agent of chickenpox (varicella) and shingles (herpes zoster). VZV and other members of the herpesvirus family are distinguished by their ability to establish a latent infection, with the potential to reactivate and spread virus to other susceptible individuals. This lifelong relationship continually subjects VZV to the host immune system and as such VZV has evolved a plethora of strategies to evade and manipulate the immune response. This review will focus on our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
424
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(441 citation statements)
references
References 173 publications
(241 reference statements)
17
424
0
Order By: Relevance
“…The viral infection could also further promote inhibition of inflammatory signaling pathways causing immunosuppression [ 57 ]. Recently, Bouwman and colleagues reported that JAK/STAT signaling system could be a valuable indicator of a strong immune response to SARS-CoV-2 infections [ 58 ]. Interestingly, another report stated that the inhibition of the JAK/STAT pathway could reduce the hyperinflammatory conditions but not the viral clearance [ 59 ].…”
Section: Role Of Jak/stat Signaling Pathway In the Immune Systemmentioning
confidence: 99%
“…The viral infection could also further promote inhibition of inflammatory signaling pathways causing immunosuppression [ 57 ]. Recently, Bouwman and colleagues reported that JAK/STAT signaling system could be a valuable indicator of a strong immune response to SARS-CoV-2 infections [ 58 ]. Interestingly, another report stated that the inhibition of the JAK/STAT pathway could reduce the hyperinflammatory conditions but not the viral clearance [ 59 ].…”
Section: Role Of Jak/stat Signaling Pathway In the Immune Systemmentioning
confidence: 99%
“…Although NETosis is a very powerful mechanism fighting for the infection, the ability of NETs to damage tissues is well-documented in infection and sterile disease. NETs directly kill epithelial and endothelial cells [11,38], and excessive NETosis damages the epithelium in pulmonary fungal infection [12] and the endothelium in transfusion-related acute lung injury [39].…”
Section: Ag Proteins and Their Role In Netosismentioning
confidence: 99%
“…In sharp contrast, VZV-infected iDCs do not undergo apoptosis, suggesting that VZV benefits from viable directly infected iDCs for virus dissemination and persistence [70,110]. In this regard, VZV selectively downregulates Fas on the surface of infected iDCs and mDCs, very likely to inhibit apoptosis of these cells [111].…”
Section: Herpesviruses Modulate Cell Survival Of Idcsmentioning
confidence: 99%